Translation on Trial: The Virginia Declaration of Rights (1776) in Sweden. Issue 1 (2nd January 2016) - Hallberg, Peter
Summary: Tracing the international career of the 1776 Virginia Declaration of Rights to Sweden via France, this article is a study in the translation of politics and the politics of translation. Specifically, it shows how the Swedish translator, physician and publisher Lorents Münter Philipson (1765–1851) reached for it in 1792 to add to domestic arguments against hereditary office, the purpose of which, the article argues, was to revive and legitimise a more indigenous but by now slumbering rights revolution. The article first outlines the reception of America in Sweden and the ways in which Sweden figured in American debates. It then provides a detailed analysis of the trial that ensued as a response to the Swedish translation of the Virginia Declaration. Having reconstructed the process of transmission and the trial, during which the translator was charged with attacking Sweden's monarchical constitution by means of 'wrongly' translating the term 'magistrate', the article places the translation of the declaration in political context. The contextual analysis shows that translating the declaration at this particular point in time makes most sense against the background of the events unfolding in revolutionary France, which the translator hoped would influence political developments in Sweden and which the authorities sought to suppress.